A Study of Determinants of Brand Loyalty in Cosmetics for Women Consumers of Pune City Using Path Analysis via Regression - Srivastava, Mukta (Indian Journal of Marketing, 2016)
With increasing competition in the cosmetic sector, nowadays, consumers are repeatedly flooded with information on different brands in the same product category of cosmetics. In such a situation, it might be a very costly affair for a company to ensure brand loyalty amongst existing customers. As a result, it has become imperative for the marketers to have a greater knowledge of the determinants of brand loyalty, that is, the factors that influence consumers to become and remain loyal to a particular brand of cosmetics. In the present article, an attempt has been made to determine the various determinants of brand loyalty in cosmetics for women consumers of Pune city. This study is important, as it will allow the marketers of cosmetic brands in Pune city to focus on the major determinants that will enable them to win and retain loyal customers rather than trying to take care of all the influencing factors. The research paper is based on primary data, which was collected from 597 women (aged between 18-58 years through personal administered survey and questionnaire answered through web-based survey). Data were analyzed using computer softwares like SPSS and Microsoft Excel. Various statistical techniques like chi-square test, factor analysis, multiple regression analysis, path analysis via regression (with correlation matrix input), and so forth were used for analyzing the data.